2016
DOI: 10.18203/issn.2455-4510.intjresorthop20163126
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of calcaneal spur in Indian population with heel pain

Abstract: <p class="abstract"><strong>Background:</strong> This is an observational study that was carried out to find out the incidence of calcaneal spur among Indian population with heel pain as it is one of the most commonest complaints of patients coming to out-patient departments.</p><p class="abstract"><strong>Methods:</strong> Radiological assessment with 200 ankle lateral view x rays were taken for patients (100 male and 100 female) with complaints of heel pain.<stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
3
6
1
Order By: Relevance
“…In the present study, incidence of only plantar spur was found to be more as compared to Achilles spur or both combined as compared to the study by Lourdes RK et al [8] In present study, incidence of calcaneal spurs among women is 62% which is comparable to study by Lourdes RK et al [8] In the study by Lourdes RK et al (ref no) incidence of calcaneal spur among women was 60%. Lourdes RK et al (ref no).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In the present study, incidence of only plantar spur was found to be more as compared to Achilles spur or both combined as compared to the study by Lourdes RK et al [8] In present study, incidence of calcaneal spurs among women is 62% which is comparable to study by Lourdes RK et al [8] In the study by Lourdes RK et al (ref no) incidence of calcaneal spur among women was 60%. Lourdes RK et al (ref no).…”
Section: Discussionsupporting
confidence: 72%
“…The other causes may be due to neurological conditions such as tarsal tunnel syndrome or entrapment of nerve to abductor digiti quinti, degenerative disc disease radiation toward heel, systemic disease (eg, reiter's syndrome, psoriartic arthritis, acute tear of plantar fascia, and calcaneal apophysitis). [7] In present study, incidence of calcaneal spurs in patients with posterior heel pain presenting to outpatient orthopaedic department is 72%, which is slightly higher compared to a study by Lourdes RK et al [8] In the study by Lourdes RK et al, [8] incidence of calcaneal spur was 59% In present study, incidence of spurs both in plantar site and at the site of insertion of Achilles was found to be 25% of total calcaneal spurs as compared to the study by Lourdes RK et al [8] In the study by Lourdes RK et al, [8] incidence of spurs both in plantar and Achilles insertion was 24%.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A recent study was done to see the changes in woman's using high heels suggested that changing from flat footwear to high heels induces chronic muscle shortening associated with discomfort, reduced shock absorption, fatigue, and increased risk of misbalance and fall leading to ankle and other serious injuries. The study also suggests that in chronic adaptation to any function movement by muscles gradually adjusts to its new functional length by a chronic loss of sarcomeres in series that may lead to farther complications of that joint like reduce joint freedom of movement (5) . This also holds true in other conditions like sudden overweight, prolonged standing, paralysis, muscular atrophy, and muscular dystrophy etc.…”
Section: Introductionmentioning
confidence: 83%
“…Its prevalence among women could be correlated with footwear, obesity and pregnancy resulting in excessive compressive forces acting at the calcaneum over a period of time. The low incidence of any type of spur in age group less than 30 years suggested that spurs do take a long time to build up 15 . This probably is because the enthesis organ dissipates the stress away from the bony insertion, this can explain why the pathological changes take place adjacent to the enthesis as well as at them.…”
Section: Discussionmentioning
confidence: 99%